Time-to-Event Modeling of Left- or Right-Censored Toxicity Data in Nonclinical Drug Toxicology. (21st May 2018) - Berges, Alienor; Cerou, Marc; Sahota, Tarjinder; Liefaard, Lia; Ambery, Claire; Zamuner, Stefano; Chen, Chao; Hénin, Emilie
Abstract: A time-to-event (TTE) model has been developed to characterize a histopathology toxicity that can only be detected at the time of animal sacrifice. The model of choice was a hazard model with a Weibull distribution and dose was a significant covariate. The diagnostic plots showed a satisfactory fit of the data, despite the high degree of left and right censoring. Comparison to a probabilistic logit model shows similar performance in describing the data with a slight underestimation of survival by the Logit model. However, the TTE model was found to be more predictive in extrapolating toxicity risk beyond the observation range of a truncated dataset. The diagnostic and comparison outcomes would suggest using the TTE approach as a first choice for characterizing short and long-term risk from nonclinical toxicity studies. However, further investigations are needed to explore the domain of application of this kind of approach in drug safety assessment.